(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The successful waste management programme, well managed, enhances the country’s health and environmental quality. This survey examines the position of the management of solid waste in the district town. For primary data collection covering around 70 to 90 randomly selected populations, the questionnaire was used. This survey is useful for people to raise awareness of waste management. Households were not aware of waste recycling, reuse & reduction of various organic or organic waste. Compared to the rest of the defined administrative area, small district town is defined. It is an important issue to identify backwardness, which is the urgent need for growth. This paper uses available data from Katwa Municipality to try the block level backwardness index.